MAPT enhancer containing rs242557 regulates multiple neighboring genes in human microglial cell line. (December 2021) - Das, Rueben G; Choi, Eirene; Jiang, Ming; Dombroski, Beth A.; Schellenberg, Gerard D.
Abstract: Background: Microtubule associated protein tau (MAPT) is involved in assembly and stabilization of microtubules. However, mutated or misfolded forms are commonly found to aggregate in Frontotemporal dementia (FTD), Progressive supranuclear palsy (PSP), Corticobasal degeneration (CBD) etc. singly or with another protein as in Alzheimer's disease (AD). The second strongest signal in MAPT locus after H1 haplotype, as identified by multiple GWAS on AD, PD, PSP and CBD, is from MAPT intronic SNP rs242557. It is part of a FANTOM5 enhancer in eye and brain and evolutionarily conserved from humans to armadillo. While it has been hypothesized that rs242557 could exert an effect on MAPT splicing, the results are contradictory. Strong, Independent signals from MAPT neighboring genes KANSL1, NSF LRR37A and WNT3 have also been noted in some of these diseases. In this study we investigate the role of the enhancer region encompassing rs242557 in gene regulation within MAPT locus. Method: Established CRISPR‐Cas9 editing protocols were used to delete rs242557 and its flanking sequences in human microglial clone 3 (HMC3) and human neuroblastoma (NBL‐S) cell lines. Heterozygous and homozygous clones with deleted rs242557 and its flanking sequences were individually selected for the study. Cells that went through the entire process of genome editing protocol without the presence of any guide RNA were used as wild type controls. cDNA, synthesized from extracted RNA were used to study expression of MAPT isoforms and its neighboring genes by qRT‐PCR, while western blots were performed from the corresponding proteins. Result: HMC‐3 cells had significant reduction (p=0.0001) of Nsf, Kansl1, Kansl1‐AS1, LRR37A, LRR37A2 and LRR37A3 transcripts in both rs242557 homozygous and heterozygous deletion clones. Total MAPT, MAPT isoforms (3R, 4R, 0N, 1N and 2N) and CRHR1 were also low with some having ct values beyond 33. At the protein level reduced expression of NSF and KANSL1 were noted in the homozygotes and some heterozygotes. No significant alteration was observed in the NBL‐S clones. Experiments are currently in progress for the remaining neighboring proteins. Conclusion: Our results indicate that the enhancer encompassing rs242557 alters expression of MAPT and several of its neighbors in HMC‐3 but not NBL‐S cells.